Attitude towards Javanese Language: A Case Study of English Department Students in Brawijaya University, Indonesia - Destyana Cory Prastiti; Emy Sudarwati (Yayasan Visi Intan Permata, 2020)
This study aims to scrutinize the attitude of Javanese youth towards their use of local language. There are two research questions proposed in this study such as namely: 1) how is the attitude of Javanese youth towards their local language, 2) what are the factors that effect on their attitudes. The objectives of this study are to define the attitude of Javanese youth towards their local language and to discover why they are behaving so. Furthermore, this study adopted qualitative method applying descriptive analysis and selected the students of English Department of Batch 2014 Batch in Brawijaya University as the participants. The results showed that the subjects indicated showed both positive and negative attitudes towards the use of Javanese language depending on the context. The positive attitude was frequently revealed on questions related to their efforts in conserving Javanese as the local language, while the negative attitude was mostly reflected on the statements associated with their language preference in daily life. Moreover, there are several factors affecting their language attitudes namely the Javanese language internal system, social and traditional, and the prestige and the power of language.